Nationwide surveillance of the antimicrobial susceptibility of Chlamydia trachomatis from male urethritis in Japan. Issue 9 (September 2016) - Takahashi, Satoshi; Hamasuna, Ryoichi; Yasuda, Mitsuru; Ishikawa, Kiyohito; Hayami, Hiroshi; Uehara, Shinya; Yamamoto, Shingo; Minamitani, Shinichi; Kadota, Junichi; Iwata, Satoshi; Kaku, Mitsuo; Watanabe, Akira; et al.
Abstract: Genital chlamydial infection is a principal sexually transmitted infection worldwide. Chlamydia trachomatis can cause male urethritis, acute epididymitis, cervicitis, and pelvic inflammatory disease as sexually transmitted infections. Fortunately, homotypic resistant C. trachomatis strains have not been isolated to date; however, several studies have reported the isolation of heterotypic resistant strains from patients. In this surveillance study, clinical urethral discharge specimens were collected from patients with urethritis in 51 hospitals and clinics in 2009 and 38 in 2012. Based on serial cultures, the minimum inhibitory concentration (MIC) could be determined for 19 isolates in 2009 and 39 in 2012. In 2009 and 2012, the MICs (MIC90 ) of ciprofloxacin, levofloxacin, tosufloxacin, sitafloxacin, doxycycline, minocycline, erythromycin, clarithromycin, and azithromycin were 2 μg/ml and 1 μg/ml, 0.5 μg/ml and 0.5 μg/ml, 0.125 μg/ml and 0.125 μg/ml, 0.063 μg/ml and 0.063 μg/ml, 0.125 μg/ml and 0.125 μg/ml, 0.125 μg/ml and 0.125 μg/ml, 0.016 μg/ml and 0.016 μg/ml, and 0.063 μg/ml and 0.063 μg/ml, respectively. In summary, this surveillance project did not identify any resistant strain against fluoroquinolone, tetracycline, or macrolide agents in Japan.